Forgotten Veterans, Invisible Memorials : How American Women Commemorated the Great War, 1917-1945 - Finkelstein, Allison S. (Book collections on Project MUSE., 2021)
"Investigates the ground-breaking role American women played in commemorating those who served and sacrificed in World War I"--